Comparison of postthawing sperm motility recovery between cryopreserved with and without cryoprotective agent using 4 different cryopreservationmethods - Irwan Taufiqur Rachman, Hilwah Nora Shofwal Widad (Universitas Gadjah Mada, 2012)
Frozen-thawed human spermatozoa are routinely used for many assisted reproduction program.However, cryopreserved spermatozoa was reported to yield lower pregnancy rates compared tofresh semen in both intra uterine inseminations and in vitro fertilization/intracytoplasmic sperminjection (IVF/ICSI) due to the reduction of sperm motility and viability induced by cryopreservationprocedures. This study was aimed to evaluate the influence of cryoprotective agent (CPA) andcryopreservation methods on human sperm motility. This was a quasi experimental study. Thirtyseven normozoospermic semen samples collected in Permata Hati Infertility Clinics of Dr. SardjitoGeneral Hospital, Yogyakarta were recruited. Four different cryopreservation methods were appliedusing and without CPA (TEST-yolk buffer). In simple two steps freezing, cryostraw were graduallyfrozen from 8 to -4°C. In simple graduated freezing, cryostraus were directly frozen at -4°C. Invapor phase freezing method, the samples in cryostraw were placed 1 cm above liquid nitrogen.In the last method, the samples were directly submerged into liquid nitrogen. Thawing wasconducted by incubation at 37°C for 5 minutes. The sperm motility recovery after cryopreservationin the 4 different cryopreservation methods was evaluated and analyzed by analysis of variance(ANOVA). The fresh sperm motility before cryopreservation was 52.9 ± 4.50%. The recovery ofmotile sperms was 17.00 ± 7.83%, 20.96 ± 5.81%, 15.06 ± 8.55% and 15.68 ± 8.3%, whenusing CPA and 5.63 ± 4.63%, 5.47 ± 3.95%, 4.45 ± 4.46% and 6.08 ± 5.06% when withoutCPA following direct plunge to liquid nitrogen freezing, vapor liquid nitrogen freezing, simplegraduated freezing and simple 2-steps freezing, respectively. Among methods using CPA, thevapor phase method resulted in highest sperm motility recovery. In methods without CPA, nosignificant difference of sperm motility recovery was observed among the 4 differentcryopreservation methods. In conclusion, the use of CPA for cryopreservation improves spermmotility recovery.